Upaya Peningkatan Kesadaran Masyarakat terhadap Pengelolaan Sampah melalui Program Edukasi Visual di Desa Buniwangi - Hamdan Ridwan, Endan; Rohmatin, Alfa; Aditia Putra; Nizar Fauzi Rachman; Salsabila Fitrah Insani; Novita Ramadhani (Lembaga Pengembangan Kinerja Dosen, 2025)
Waste remains one of the major environmental issues and a serious challenge in rural communities. The lack of discipline in waste disposal and limited knowledge of the impact of non-biodegradable waste have contributed to declining environmental quality and potential health problems. In Buniwangi Village, Pagelaran Subdistrict, Cianjur Regency, these conditions highlight the need for educational programs that provide practical understanding while fostering community awareness. This community service activity aimed to improve residents’ awareness of waste management through visual education media in the form of information boards displaying the decomposition time of various types of waste, ranging from organic to non-organic materials. The implementation method applied an asset-based community development (ABCD) approach, emphasizing active community participation. The program was carried out in three main stages: preparation, implementation, and evaluation. The preparation stage included location surveys, needs mapping, and obtaining permission from village authorities. The implementation stage involved designing attractive educational boards, installing them at strategic points in the village, and conducting socialization to explain the information provided. The evaluation stage was carried out through direct observation and short interviews to assess the program’s impact on community knowledge and behavior.The results indicated an improvement in residents’ understanding of the differences between biodegradable and non-biodegradable waste. Villagers began to show awareness of reducing single-use plastics and started applying the 3R principles (reduce, reuse, recycle) in daily life. Overall, this program had a positive impact by fostering greater environmental concern and became an initial step toward building a sustainable waste management culture in Buniwangi Village.